Identification of cellular immunoglobulins in chronic lymphocytic leukaemia by immunoperoxidase staining. Issue 12 (December 1983) - Markey, G M; McConnell, R E; Alexander, H D; Morris, T C; Robertson, J H
Abstract : An indirect immunoperoxidase technique has been used for visualisation of cellular immunoglobulins in chronic lymphocytic leukaemia. Baker's formol calcium was used as fixative. Monoclonal light and heavy chain patterns were demonstrated in 24 out of 27 cases. Only one case did not have any demonstrable immunoglobulins. The presence of alpha or gamma heavy chain immunoglobulin isotypes in leukaemic lymphocytes was found to be related to low mouse rosetting capacity (p less than 0.05).